Pericyte dysfunction due to Shb gene deficiency increases B16F10 melanoma lung metastasis. Issue 9 (30th May 2020) - He, Qi; Li, Xiujuan; He, Liqun; Li, Yousheng; Betsholtz, Christer; Welsh, Michael
Abstract: Intravasation, vascular dissemination and metastasis of malignant tumor cells require their passage through the vascular wall which is commonly composed of pericytes and endothelial cells. We currently decided to investigate the relative contribution of these cell types to B16F10 melanoma metastasis in mice using an experimental model of host Shb gene (Src homology 2 domain‐containing protein B) inactivation. Conditional inactivation of Shb in endothelial cells using Cdh5‐CreERt2 resulted in decreased tumor growth, reduced vascular leakage, increased hypoxia and no effect on pericyte coverage and lung metastasis. RNAseq of tumor endothelial cells from these mice revealed changes in cellular components such as adherens junctions and focal adhesions by gene ontology analysis that were in line with the observed effects on leakage and junction morphology. Conditional inactivation of Shb in pericytes using Pdgfrb‐CreERt2 resulted in decreased pericyte coverage of small tumor vessels with lumen, increased leakage, aberrant platelet‐derived growth factor receptor B (PDGFRB) signaling and a higher frequency of lung metastasis without concomitant effects on tumor growth or oxygenation. Flow cytometry failed to reveal immune cell alterations that could explain the metastatic phenotype in this genetic model of Shb deficiency. It is concluded that proper pericyte function plays a significant role in suppressing B16F10 lung metastasis. Abstract : What's new? Intravasation, vascular dissemination, and metastasis of malignant tumor cells requires their passage through the vascular wall. The relative contributions of vascular wall endothelial cells and pericytes have been difficult to assess, however, due to the interdependence of these cell types. Here, the authors demonstrate, by using a genetic model of Shb ‐gene inactivation in endothelial cells and pericytes, that pericyte dysfunction increases melanoma metastasis to the lung. Aberrant platelet‐derived growth factor receptor B signaling in pericytes plays a key role in increasing metastasis. The findings highlight ameliorating pericyte dysfunction in malignant tumors as a strategy to prevent metastasis in malignant disease.